Rancang Bangun Hypobaric storage Sebagai Alat Penyimpanan Cabai Rawit (Capsicum frutescens L.) - Dewi Maya Maharani; Anang Lastriyanto; Vibi Rafianto; Sonia Verent Yudi Santo Putri; Kharimatul Khasanah (agriTECH, 2019)
Chili is a superior commodity that is much needed by Indonesian people. This commodity is susceptible to damages such as weight loss, decreased vitamin C content, color fades, and decay, which causes reduced shelf life. An improper storage process accounts for about 30% damage to chili. The objective of the research was designing a chili storage tool based on the hypobaric system which can decrease the respiration rate and ethylene gas, thus expending the shelf life. This tool consisted of several components, namely storage room, reservoir tank, vacuum pump, control panel, and a table. The research method included design and instrument, also pepper quality testing. Hypobaric storage used a pressure of -60 (-55) kPa, and a temperature of 22.9 °C. The results showed that the hypobaric storage design, instrument automation ran well, and the chili with hypobaric storage had minimal weight loss, water content, and vitamin C degradation, at 3.28%, 1.05%, and 12.91%. Parameters alteration based on entitlement with refrigerator were 6.66%, 6.8%, and 48.61%, whereas with room temperature the results were 9.7%, 15.98%, and 52.17%. Hypobaric storage for Chili was able to keep the chili quality better than room temperature and refrigerator.